A Transnational Study on the Contribution of the Education, Land, Physical Capital, Labor, and Unemployment Ratio to Economic Development - Fang-Chung Chang (National Taipei University of Education, 2020)
Human capital, land resources, capital, labor, and unemployment rates is closely related to national development. However, among these production factors and the unemployment rate, which is the most important to economic development? The aim of this study was to analyze the contribution of these factors to gross domestic per capita in 2010, 2015, and 2016, respectively. The results were as follows: The land resource, capital, labor, and the higher education enrolment rate have a significant and positive impact on development. Specifically the explanatory power of higher education enrolment rate to development was between 29.4% and 31.1%, which was the most important among the production factors. The other factors were important behind the higher education enrolment rate in the three years, but these factors also significantly contributed to the development between 2.2% and 10.5%. In the three years, the unemployment rate had significantly and negatively affected development, and its explanatory power for the development was 2.2%, 2.8%, and 5.2%, respectively. These meant that in the process of development, besides higher education enrolment rate being the key factor that impacts development, the unemployment rate also played a significant role which cannot be ignored. Thus countries continue investing in human capital, and reducing unemployment are important strategies for development. Human capital theory was proven to have practical inspiration, innovation and contribution beyond the development.